RISK FACTORS AND OUTCOMES IN PATIENTS WITH SEVERE NECROTIZING FASCIITIS ADMITTED TO SURGICAL INTENSIVE CARE UNIT: A RETROSPECTIVE COHORT STUDY FROM PAKISTAN - Khan, Muhammad Faisal; Mistry, Akbar Azizullah; Usmani, Ayesha Shabbir; Shamim, Faisal (Journal of Ayub Medical College Abbottabad, 2024)
Background: Necrotizing fasciitis (NF) is a debilitating condition that has high mortality and morbidity even in specialized centres. This study aims to determine risk factors in our local population and identify variables that contribute to mortality in the necrotizing fasciitis patients treated in the surgical intensive care unit of a tertiary care hospital Methods: This retrospective cross-sectional study included 39 patients admitted to the surgical ICU from January 1, 2015 to June 30, 2019. They were analyzed for comorbidities, symptoms at presentation, predisposing factors, location of the infection, microbiological analysis and mortality. Results: There were 27 (69.2%) males and 12 (30.8%) females while the age was distributed as 47.44±15 years. Pain was the most frequently reported symptom (89.7%), followed by swelling (79.5%) and tenderness (77%). Significant predisposing factors included trauma in 14 (35.9%) and Intramuscular injections (IM) in 10 (25.6%) patients. On univariate and multiple logistic regression, patients with chronic kidney disease (AOR:1.27, 95% CI: 0-691.22) and ischemic heart (AOR: 1.55, 95% CI: 0.02-153.26) disease had higher odds of mortality than those with no comorbidity. The overall mortality was 12/39 (30.8%). Conclusion: Intramuscular injections without aseptic measures in our local population are a significant predisposing risk factor for severe necrotizing fasciitis. High laboratory risk Indicator for necrotizing fasciitis and acute physiology and chronic health evaluation II scores at admission were associated with increased mortality.